Profile of training and skilling programs in the Philippines - Aniceto C. Orbeta; John Paul P. Corpus (Philippine Institute for Development Studies (PIDS), 2021)
This study is undertaken as part of the Youthworks PH initiative by the Philippine Business for Education. It aims to address five research questions: (a) What are the existing training programs for the priority sectors of YouthWorks PH (construction, manufacturing, and tourism)? (b) How responsive are the current training programs to the needs of industries? (c) Is there industry demand for new National Certificates in specific sectors and for what level and occupation? (d) How did the Covid-19 pandemic change the landscape of training programs in the country? (e) What are the emerging industry sectors brought about by the Covid-19 pandemic? Secondary data and interviews with relevant stakeholders, particularly with training providers in YouthWorks PH priority sectors, were used in this study. TVET providers are overwhelmingly private, but public providers account for a larger share of graduates. Most TVET graduates are products of either community-based or institution-based TVET programs. TVET programs and graduates are concentrated in a few occupational sectors, the dominant sector being Tourism (Hotel and Restaurant). Likewise, demand for assessment leading to a National Certificate is concentrated in relatively few qualifications. The government offers several scholarships promoting TVET access. The issues on the responsiveness of current programs, according to the respondents, revolves around: (a) the lack of demand, particularly for construction; (b) weaknesses in the design of financing programs; (c) perception about the quality of training schools, trainers and assessors; and (d) training content. Industry respondents noted demand for skills standardization in prefabricated construction, supervisory-level construction jobs, and nursing assistance. Restrictions due to Covid-19 resulted in the suspension or scaling down of training programs. Some providers have provided online modules, but lack of access to appropriate digital devices or the internet hinders remote learning. Covid-19 has caused the emergence of online food selling and made digital skills valuable. The study recommends pursuing an information campaign to promote construction jobs; reviewing and rationalizing TVET financing programs; reviewing the TVET content; tapping industry practitioners as trainers and assessors; investing in flexible learning modalities; and promoting regular dialogue between the government, employers, and TVET providers.
Keywords: 330; TVET; technical-vocational education; training